Female education in Nicaraguan society: a nuisance for the Liberal Revolution (1893-1909) - Zosa-Cano, Alexander (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: Analyze the purposes and educational programs of the conservative model for female education, in antithesis with the economic, political, and social projection of the Nicaraguan Liberal Revolution (1893-1909). Originality/contribution: this work contributes to the historiographic study of women from an academic perspective, in contrast to the economic, political, and social projection of the Liberal Revolution. Method: This is a qualitative research. The study programs and cultural spaces of this new process of conservative education in an era that proclaims freedom were examined through bibliographic and hemerographic review. Strategies/Data collection: Documentary information from the Biblioteca del Banco Central de Nicaragua, the Instituto de Historia de Nicaragua y Centroamérica (IHNCA-UCA), and  the  Biblioteca Nacional de Nicaragua were compiled and organized. Conclusions: 1) The purpose of female education during the Liberal Revolution was to prepare women for married life and the raising of their children; however, women took advantage of the opportunities assigned by the State as educators at the kindergarten, primary, and secondary levels to transmit their ideas in favor of women. Years later, they or their students would lead the birth of the women's fight in Nicaragua. 2) The modern curriculum for female education was a farce. The curricula of the Colegio de Señoritas de Granada, adapted by the North American teachers, were eliminated to establish the training of women for domestic life. 3) It should be emphasized that during the sixteen years of the Liberal Revolution, the bourgeoisie introduced Europeanized life models into the country. These differences settled in society and were expressed in women's education. The model of women's education was meant to be functional for the family and that of men was for society and decision-making in politics, economy, and family. Liberalism was transformative, but it limited women to the minimum expression, becoming the most faithful antithesis of a revolution.